ROLE OF CRANIAL COMPUTED TOMOGRAPHY IN PREDICTING CLINICAL OUTCOME IN PATIENTS WITH MINOR HEAD INJURY - Afzal, Tayyaba; Akram, Faiza; Durrani, Misbah (Journal of Ayub Medical College Abbottabad, 2013)
Background: Optimal management of patients with mild head injury in the emergency department is still under debate. The objective of this study was to determine the diagnostic efficacy of computed tomography in patients with minor head injury. Methods: A cross-sectional comparative study was conducted in the Radiology department of PIMS, Islamabad in collaboration with neurosurgery department from 14 February to 13 August 2008. One hundred and sixty patients coming to accident and emergency department with minor head injury with GCS of 13-15 were included. The patients then underwent non contrast enhanced CT of brain within 6 hours and results of computed tomography were compared with clinical outcome determined at 24 hours. Results: Twenty-two patients were CT positive for intracranial injury. Out of these 18 patients had an adverse clinical outcome and were considered true positive, while 4 patients were false positive and had normal clinical course with observation only. Ninety-four patients were CT negative for intracranial injury. Out of these 93 were true negative while 1 was false negative, as confirmed subsequently by adverse clinical outcome. The sensitivity, specificity, positive and negative predictive values and diagnostic efficacy of CT for intracranial injury in patients of minor head injury was 94%, 96%, 81%, 99% and 95.7% respectively. Conclusion: CT should be used as a primary screening investigation in all patients with minor head injury as patients with normal neurological examination and normal CT scan can be safely discharged without need for inpatient or patient observation, thereby making the hospital resources available for more serious patients. Keywords: Intracranial injury, Computed tomography, Diagnostic efficacy, Minor head injury